Modeling and simulation of drum height adjusting system of shearer - CHEN Jinguo; LIU Chunsheng; FAN Jianhong; ZHANG Yanjun; WAN Feng (Gong-kuang zidonghua, 2017)
In order to improve dynamic performance and tracking reliability of drum height adjusting system of shearer, mathematical models of drum height and hydraulic cylinder displacement were established by analyzing work principle of the drum height adjusting system and relationship of geometric parameters of hydraulic mechanism. Combining fuzzy adaptive PID controller, simulation models of open loop controlled and closed loop controlled drum height adjusting systems based on electric-hydraulic proportional direction valve controlling hydraulic cylinder were established in Automation Studio software. Speed response and location tracking characteristics of the systems were studied under no-load and load conditions separately. The simulation results show that the systems have fast response speed and better goodness of fit of drum location tracking, and performance of the closed loop controlled drum height adjusting system is better than the open loop controlled one.